Increasing Number and Proportion of Adverse Obstetrical Outcomes among Women Living with HIV in the Ottawa Area: A 20-Year Clinical Case Series - Sarah Buchan; Katherine A. Muldoon; Johanna N. Spaans; Louise Balfour; Lindy Samson; Mark Walker; D. William Cameron (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. The prevalence and associated risks with adverse obstetrical outcomes among women living with HIV are not well measured. The objective of this study was to longitudinally investigate the prevalence and correlates of adverse obstetrical outcomes among women with HIV. Methods. This 20-year (1990–2010) clinical case series assessed the prevalence of adverse obstetrical outcomes among pregnant women with HIV receiving care at The Ottawa Hospital (TOH). General estimating equation modeling was used to identify factors independently associated with adverse obstetrical outcomes, while controlling for year of childbirth clustering. Results. At TOH, there were 127 deliveries among 94 women (1990–2010): 22 preterm births, 9 births with low birth weight, 12 births small for gestational age, and 4 stillbirths. Per year, the odds of adverse obstetrical outcomes increased by 15% (OR: 1.15, 95% CI: 1.03–1.30). Psychiatric illness (AOR: 2.64, 95% CI: 1.12–6.24), teen pregnancy (AOR: 3.35, 95% CI: 1.04–1.46), and recent immigrant status (AOR: 7.24, 95% CI: 1.30–40.28) were the strongest correlates of adverse obstetrical outcomes. Conclusions. The increasing number and proportion of adverse obstetrical outcomes among pregnant women with HIV over the past 20 years highlight the need for social supports and maternal and child health interventions, especially among adolescents, new immigrants, and those with a history of mental illness.